Decompression followed by enucleation in the treatment of orthokeratinized odontogenic cyst: case report - Boas, Jéssica Lopes Vilas; Lucamba, Agnelo Josué; Cesconetto, Lorenzzo de Angeli; Araujo, André Vitor Alves; Oliveira, Vinícius Dantas de; Provenzano, Nilton (Journal of Oral Diagnosis, 2020)
The orthokeratinized odontogenic cyst, currently classified as a separate entity from the odontogenic keratocyst, is a rare developmental cyst that affects the gnatic bones. It predo- minantly affects young male patients. Its clinical behavior is benign with a predominance of involvement by the posterior region of the mandible. Treatment involves enucleation, with or without prior decompression. The present case reports a 17-year-old male patient with bilateral lesion manifestation, the left osteolytic process being of large proportions. The patient was subjected to decompression prior to enucleation, and this conservative treatment is essential for successful treatment. The patient was followed up for 1 year with no signs of recurrence.